Causal assessment of serum urate levels in cardiometabolic diseases through a Mendelian randomization study - Keenan, Tanya; März, Winfried (Journal of the American College of Cardiology, 2016)
Background: Although epidemiological studies have reported positive associations between circulating urate levels and cardiometabolic diseases, causality remains uncertain. Objectives: Through a Mendelian randomization approach, we assessed whether serum urate levels are causally relevant in type 2 diabetes mellitus (T2DM), coronary heart disease (CHD), ischemic stroke, and heart failure (HF). Methods: This study investigated 28 single nucleotide polymorphisms known to regulate serum urate levels in association with various vascular and nonvascular risk factors to assess pleiotropy. To limit genetic confounding, 14 single nucleotide polymorphisms exclusively associated with serum urate levels were used in a genetic risk score to assess associations with the following cardiometabolic diseases (cases/controls): T2DM (26,488/83,964), CHD (54,501/68,275), ischemic stroke (14,779/67,312), and HF (4,526/18,400). As a positive control, this study also investigated our genetic instrument in 3,151 gout cases and 68,350 controls. Results: Serum urate levels, increased by 1 SD due to the genetic score, were not associated with T2DM, CHD, ischemic stroke, or HF. These results were in contrast with previous prospective studies that did observe increased risks of these 4 cardiometabolic diseases for an equivalent increase in circulating urate levels. However, a 1 SD increase in serum urate levels due to the genetic score was associated with increased risk of gout (odds ratio: 5.84; 95% confidence interval: 4.56 to 7.49), which was directionally consistent with previous observations. Conclusions: Evidence from this study does not support a causal role of circulating serum urate levels in T2DM, CHD, ischemic stroke, or HF. Decreasing serum urate levels may not translate into risk reductions for cardiometabolic conditions.